2005
DOI: 10.1111/j.0737-1209.2005.220406.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Factors Affecting Quality of Life in Diabetic Patients in Iran

Abstract: Diabetic patients face great challenges in many dimensions of QOL. Nursing instructors and nursing educators in educational centers for diabetics can use the findings of this research to assess their patients more effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
(42 reference statements)
0
16
0
Order By: Relevance
“…Generally, a negative relationship was observed between diabetes disease and quality of life which can affect physical, mental, and social aspects of individuals [9][10][11][12][13][14][15][16]. A related affecting factors on quality of life among these patients, we can point to complications of type II diabetes and underlying and demographic variables, age, gender, educational status of individuals and their family members regarding medical information, duration of disease, and economical status which have significant relationship with patient's quality of life [12,14,17]. As mentioned before, diabetes is one of the chronic diseases with rising trend throughout world especially in East Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, a negative relationship was observed between diabetes disease and quality of life which can affect physical, mental, and social aspects of individuals [9][10][11][12][13][14][15][16]. A related affecting factors on quality of life among these patients, we can point to complications of type II diabetes and underlying and demographic variables, age, gender, educational status of individuals and their family members regarding medical information, duration of disease, and economical status which have significant relationship with patient's quality of life [12,14,17]. As mentioned before, diabetes is one of the chronic diseases with rising trend throughout world especially in East Mediterranean region.…”
Section: Introductionmentioning
confidence: 99%
“…However, most of the studies on diabetes and QOL have been conducted in developed countries [12] and studies of the QOL in diabetic patients in developing countries are rare [13] [14].…”
Section: Introduction and Aim Of Studymentioning
confidence: 99%
“…The study of Ghanbari et al [21] indicated that men were less affected by diabetes diseases than women. This result of the study made us think that male patients perceived diabetes as a less serious problem.…”
Section: Discussionmentioning
confidence: 99%